DETERMINAN BEBAN PAJAK MASA DEPAN PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Yusuf, Muhammad (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
This study aims to examine the effect of tax aggressiveness components and deferred tax  assets on tax expense for the future period. Tax Aggressiveness aims to minimize  the  tax  burden  on  companies  in  accordance  with  legislation  and Deferred tax assets arise due to the difference in the time of revenue recognition. The study population consists of 115 manufacturing companies listed on the Indonesia  Stock Exchange during the period 2011-2015. Simple regression analysis and Multiple Regression Analysis are used to know the influence of each component of tax planning and  deferred tax asset to future tax expense. Tax Aggressiveness data and deferred tax assets are collected from the Financial Position Report and Notes to the Financial Statements of the Company. Research Results Indicates that Tax Aggressiveness does not affect future tax expenses. While the result of deferred tax asset has significant negative effect to future tax expense. This allows the existence of deferred tax assets will reduce the tax burden in the coming period.